Righting America at the Creation Museum - Trollinger, Susan L., 1964- (Book collections on Project MUSE., 2016)
In Righting America at the Creation Museum, Susan L. Trollinger and William Vance Trollinger, Jr., take readers on a fascinating tour of the museum. The Trollingers vividly describe and analyze its vast array of exhibits, placards, dioramas, and videos, from the Culture in Crisis Room, where videos depict sinful characters watching pornography or considering abortion, to the National Selection Room, where placards argue that natural selection doesn't lead to evolution. The book also traces the rise of creationism and the history of fundamentalism in America.